Probing for heavy neutral leptons at DUNE and ICARUS - Schezwen, Sharoz (Nanyang Technological University, 2024)
The Standard Model has for a long time been successful in describing the world around, that is, until the discovery of neutrino oscillations. This led to the understand- ing that neutrinos were not massless as originally thought, and requires physics beyond the Standard Model. A possible solution to this problem is the proposal of the existence of so called Heavy Neutral Leptons. These Heavy Neutral Leptons are proposed to mix with the Standard Model neutrino flavours, but they are much heavier than them. To fully test this theory and discover the behaviour of such new objects, methods to produce and detect them are needed. These methods allow physicists to probe into uncharted waters upon finding the Heavy Neutral Leptons, that can possibly solve more unanswered questions by the Standard Model such as why is there more matter than antimatter in the Universe? Or what is dark matter which is found abundantly in the Universe? This thesis presents contributions to the current simulations that are done at the DUNE and ICARUS experiments, by performing the sensitivity analysis of the detectors in probing for these new particles. For DUNE, the current simulations are developed further to enable adding additional features leading to a more accurate version that goes more in line with recent theoretical developments. For ICARUS, the actual background data obtained from cosmic muons, acting as noise are used to obtain the most realistic estimations of the sensitivity.